Validation of Suggested Formula for Depth of Insertion of Endotracheal Tube in Indian Children: A Prospective Observational Study - Theagrajan, Annu; Sethuraman, Raghuraman M.; Prabhu, Manjunath (Journal of Pediatric Intensive Care, 2024)
This study aimed to validate the recently suggested formula ([Age in years/2] + 10 cm) by us for depth of endotracheal tube (ETT) insertion in Indian children aged 2 to 10 years by comparing it with Cole's formula ([Age in years/2] + 12 cm). Only a few methods/formulae for depth of insertion of ETT in children have been described and validated, with no study for Indian children or other Asian ethnic populations.A total of 95 children were included. The tracheal length was calculated by adding the “black line to tube tip” distance (measured externally) with the “tube tip to carina” distance measured using a fiberoptic bronchoscope. The depth of ETT insertion based on Cole's formula and the suggested formula was calculated in each child with the head in the neutral position. The incidence and risk of endobronchial (EB) intubation, “at carina” placement of ETT, and ideal placement of ETT by both formulas were noted and interpreted.The ideal position of ETT varied significantly as per Cole's formula (p < 0.001). The incidence, risk of EB intubation, and “at carina” placement of ETT were significantly lower as per the suggested formula (p < 0.001).The suggested formula improves the possibility of ideal placement and decreases the incidence of EB placement when compared with Cole's formula.
Keywords: endotracheal tube; depth of insertion; formula validation; Indian children; Asian ethnicity